Optimalisasi Suhu Pengering pada Proses Pembuatan Tepung Asap - Masu, Anjelina Sani; Abrina Anggraini, Sinar Perbawani; Yunininggsih, Susi (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
Liquid smoke is the result of direct or indirect combustion of coconut shells (pyrolysis). Volatile compounds in liquid smoke that act as preservative activity can evaporate during storage. So it is necessary to develop technology to protect active components and facilitate their handling by making smoked flour using maltodextrin as a carrier medium. Smoked flour is a renewable energy that can be used as a food preservative which is made by encapsulating chitosan because smoked flour has a higher phenol value compared to liquid smoke. At the drying temperature of the smoked flour, namely 135áµ’C, 140áµ’C, 145áµ’C, and 150áµ’C, so that the smoked flour had an indigo content of 70.79% phenol and 11.10% acetic acid, while the phenol component in liquid smoke was 24.03% and 57.70% acetic acid. . The results showed that the drying temperature concentration of 145áµ’C showed the lowest water content with a value of 53.10%. While drying at a temperature of 135% has a higher protein content, namely 1.245%. The benefits of smoked flour to inhibit bacterial growth, the use of smoked flour can also maintain the quality of food products.